A comparative study to see the effect of different dexmedetomidine infusion doses on the hemodynamic stress response, sedation and post-operative analgesia in patients undergoing laparoscopic cholecystectomy (Journal of Pharmaceutical Negative Results, 2022)
Background and Aims: Laparoscopic surgeries involve the creation of a pneumoperitoneum which results in ventilatory and respiratory changes leading to adverse cardio-respiratory effect. The Aim of this study is to judge the effects of different dexmedetomidine infusion doses on hemodynamics of the patient during laryngoscopy, endotracheal intubation, and the creation of pneumoperitoneum in laparoscopic cholecystectomy and also to see the effect of dexmedetomidine infusion on post-operative analgesia requirements and sedation levels.Material and methods: After obtaining approval from the institutional ethical committee 88 adult patients of either sex belonging to ASA grade I and grade II admitted to our hospital, for laparoscopic cholecystectomy were divided into 4 groups 22 each group I was the control group and the other 3 groups received different doses of dexmedetomidine0.2mcg/kg/hr, 0.4 mcg/kg/hr, and 0.6mcg/kg/hr respectively.Results: The collected data were transformed into variables, coded and entered in Microsoft Excel. Data were analyzed and statistically evaluated using SPSS-PC-20 version. Statistically significant changes in Heart rate, Systolic and Diastolic BP (p<0.05) were noted between all the groups.(P<0.05) Also statistically significant changes in VAS score (p<0.05) were present between group I (Control group) and group II, III, IV.Conclusion: Dexmedetomidine infusion decreased the hemodynamic stress response and provided good sedation as well as post-op analgesia in patients undergoing laparoscopic cholecystectomy.